Composites engineering handbook - Mallick, P.K (Materials engineering (Marcel Dekker, Inc.), 1997)
Offers information on the fundamental principles, processes, methods and procedures related to fibre-reinforced composites. The book presents a comparative view, and provides design properties of polymeric, metal, ceramic and cement matrix composites. It also gives current test methods, joining techniques and design methodologies.